Melatonin: a modulator in metabolic rewiring in T-cell malignancies - Rai, Seema; Roy, Gunja; Hajam, Younis Ahmad (Frontiers in Oncology, 2024)
Melatonin, (N-acetyl-5-methoxytryptamine) an indoleamine exerts multifaced effects and regulates numerous cellular pathways and molecular targets associated with circadian rhythm, immune modulation, and seasonal reproduction including metabolic rewiring during T cell malignancy. T-cell malignancies encompass a group of hematological cancers characterized by the uncontrolled growth and proliferation of malignant T-cells. These cancer cells exhibit a distinct metabolic adaptation, a hallmark of cancer in general, as they rewire their metabolic pathways to meet the heightened energy requirements and biosynthesis necessary for malignancies is the Warburg effect, characterized by a shift towards glycolysis, even when oxygen is available. In addition, T-cell malignancies cause metabolic shift by inhibiting the enzyme pyruvate Dehydrogenase Kinase (PDK) which in turn results in increased acetyl CoA enzyme production and cellular glycolytic activity. Further, melatonin plays a modulatory role in the expression of essential transporters (Glut1, Glut2) responsible for nutrient uptake and metabolic rewiring, such as glucose and amino acid transporters in T-cells. This modulation significantly impacts the metabolic profile of T-cells, consequently affecting their differentiation. Furthermore, melatonin has been found to regulate the expression of critical signaling molecules involved in T-cell activations, such as CD38, and CD69. These molecules are integral to T-cell adhesion, signaling, and activation. This review aims to provide insights into the mechanism of melatonin’s anticancer properties concerning metabolic rewiring during T-cell malignancy. The present review encompasses the involvement of oncogenic factors, the tumor microenvironment and metabolic alteration, hallmarks, metabolic reprogramming, and the anti-oncogenic/oncostatic impact of melatonin on various cancer cells.